2016
DOI: 10.1021/acscatal.6b03135
|View full text |Cite
|
Sign up to set email alerts
|

C–H Activation and Olefin Insertion as Sources of Multiple Sites in Olefin Polymerization Catalyzed by CpAlkylHf(IV) Complexes

Abstract: Intramolecular activation of hydrocarbyls to form metallacyclic complexes is a relatively fast process in cationic hafnocene catalysts bearing propyl-substituted Cp ligands. The resulting metallacycles are effective 1-hexene polymerization catalysts with activities comparable to that of the nonmetalated precursor. Ad hoc polymerizations of 1-hexene, using (Cp Pr )2HfMe2 as catalyst precursor, allow the isolation and characterization, via nuclear magnetic resonance (NMR) and matrix-assisted laser desorption ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…In our continuing mechanistic investigations of olefin polymerization catalyzed by hafnocene derivatives, we recently reported that the [(Cp Pr ) 2 HfR][X] ion pair undergoes a relatively facile C−H activation of one propyl chain, affording the corresponding cyclometalated species [Cp Pr CpCH2CH2CH2 Hf] [X] ( 1 ) . Detailed NMR, mass spectrometry, and polymerization studies indicate that 1 can be formed under relevant polymerization conditions, enabling multiple olefin insertions into its Hf−CH 2 bond. We have hypothesized that these irreversible in situ catalyst alterations may generate several different active species.…”
Section: Introductionmentioning
confidence: 66%
“…In our continuing mechanistic investigations of olefin polymerization catalyzed by hafnocene derivatives, we recently reported that the [(Cp Pr ) 2 HfR][X] ion pair undergoes a relatively facile C−H activation of one propyl chain, affording the corresponding cyclometalated species [Cp Pr CpCH2CH2CH2 Hf] [X] ( 1 ) . Detailed NMR, mass spectrometry, and polymerization studies indicate that 1 can be formed under relevant polymerization conditions, enabling multiple olefin insertions into its Hf−CH 2 bond. We have hypothesized that these irreversible in situ catalyst alterations may generate several different active species.…”
Section: Introductionmentioning
confidence: 66%
“…Metallocenes are industrially relevant chemical catalysts for polyolefin production. In the past, numerous efforts [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have been made to understand the behavior of group 4 metallocenes in olefin polymerization. Metallocenes require cocatalysts to make active catalyst species (ion pair formation), [20][21][22][23] and modification in and/or changing cocatalysts lead to significant changes in catalyst performance.…”
Section: Introductionmentioning
confidence: 99%
“…Metallocenes require cocatalysts to make active catalyst species (ion pair formation), [20][21][22][23] and modification in and/or changing cocatalysts lead to significant changes in catalyst performance. [1,3] Many cocatalyst species have been used in metallocene such as aluminiumbased (MAO, [12,24] Al(R) 3 [25] and Al(C 6 F 5 ) 3 [26,27] ), boron-based (B-(C 6 F 5 ) 3 , [1][2][3]20,21] [CPh 3 ] + [B(C 6 F 5 ) 4 ] À , [1,3] ([B(C 6 F 5 ) 4 ] À [Me 2 NHPh] + ), [28] ). The aluminium-based cocatalysts (MAO and Al(R) 3 ) are extensively used for olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Ti benzyl- or allyl-type complexes can be inferred from the polymer microstructure, but to the best of our knowledge, no direct experimental evidence has ever been reported for their formation under polymerization conditions. NMR spectroscopy has emerged as a suitable technique to trap and detect elusive species, ,, and 1-X 2 (X = Me, Bn) was regarded as the ideal candidate for such studies . Herein, we report NMR evidence for the successful capture of these Ti species under catalytic conditions.…”
mentioning
confidence: 95%